3D-QSAR study on ether and ester analogs of artemisinin with comparative molecular field analysis - Jiang Hua-liang; Chen Kai-xian; Wang Hong-wu; Tang Yun; Chen Jian-zhong; Ji Ru-yun (Acta Pharmacologica Sinica, 2016)
Comparative molecular field analysis (CoMFA), a three-dimensional quantitative structure-activity relationship (3D-QSAR) paradigm, was used to study the correlations between the physicochemical properties and the in vitro activities of a series of ether and ester analogs of artemisinin. Four alignment models were used in the CoMFA investigation. The correlations derived from CoMFA analysis with the four alignments proved all to have good predictive values. The steric field predictive model of alignment B is accordant with the experimental results of Avery M A, et al: J Med Chem 1993; 36: 4264-75. The electrostatic field predictive results of alignments A, B, and C are consistent with our previous result of quantum chemical calculation. The highest rcross2 of alignment D, indicated that the side chain of -C6-O2-O1-C10-O3-C7-O4-C12-O5- and atom C16 are important groups of artemisinin analogs for antimalarial activity.